The overland journey from Utah to California : wagon travel from the City of Saints to the City of Angels - Lyman, Edward Leo, 1942- (University of Nevada Press, 2004)
"Historian Edward Leo Lyman has provided the first history of the complete Southern Route, and of the people who developed and used it. Based on extensive research in primary sources - including many early travelers accounts - and on Lyman's own investigation of the route and its branches, the book discusses the exploration and development of the Old Spanish Trail. Its horse thieves and traders, including Jedediah Smith and Kit Carson, along with government explorer John C. Fremont. Developing the old pack mule trail as a wagon road between Salt Lake City and Los Angeles, miners heading for the California gold fields first used the route extensively
Keywords: Overland journeys to the Pacific.; Trails -- West (U.S.) -- History -- 19th century.; Frontier and pioneer life -- West (U.S.); Wagon trains -- West (U.S.) -- History -- 19th century.; Pioneers -- West (U.S.) -- History -- 19th century.; Latter Day Saint pioneers -- West (U.S.) -- History -- 19th century.; West (U.S.) -- Description and travel.; West (U.S.) -- History, Local.; Voyages par terre jusqu'au Pacifique.; États-Unis (Ouest) -- Descriptions et voyages.; HISTORY -- State & Local.; Frontier and pioneer life; Latter Day Saint pioneers; Overland journeys to the Pacific; Pioneers; Trails; Travel; Wagon trains; West United States; Migration; Utah; Frontier; Kalifornien; Geschichte 1800-1900.; American history: c 1800 to c 1900 -- c 1800 to c 1900 -- Western & Pacific Coast states.; Social & cultural history -- c 1800 to c 1900 -- Western & Pacific Coast states.; History.; Pioneers -- Utah.; United States, West -- Description and travel.; United States, West -- History.; United States, West -- Migration, Internal.; 1800-1899; History; Local history